Silicon Quantum Dots Derived From Zinc Oxide Incorporated Porous Silicon For Photovoltaic Applications - Almomani, Mohammad Samir Ali (2022)
The transition metals were used to enhance the optical properties of the semiconductor. Zinc (Zn) was inserted in porous silicon (PSi) and silicon quantum dots (Si QDs) to improve the optical properties by reducing oxidation. The colloidal Si QDs integrated with Zn oxide (ZnOSi QDs) were obtained from the electrochemically etched PSi with Zn inclusion followed by the sonication, that process called the top-down process. The emission spectra of the studied ZnOSi QDs were mainly ascribed to the effects of quantum confinement and zinc oxide (ZnO) surface layer on the Si QDs that minimized the Si oxidation. The combining top-down and bottom-up processes led to producing ZnOSi QDs of various bandgaps depending on the particles size; hence drawbacks encounter Si QDs such as the challenge to produce particles of uniform size and Si QDs oxidized after the electrochemical process due to ambient exposure, were exceeded. The bottom-up method was used to reproduce these ZnOSi QDs with various uniform sizes and shapes by regrowth of the Si QDs, which ZnO covered. Thin films containing titanium dioxide nanoparticles (TiO2 NPs) were prepared from titanium hydroxide (Ti(OH)4). Spherical TiO2 NPs of average size in the range of 3.2 nm to 33.94 nm were utilised to improve the extraction of photo-generated charges. The graded bandgap quantum dots solar cells (GBQDSCs) were fabricated based on non-toxic materials such as Si QDs and TiO2 NPs. ZnOSi QDs layers of various sizes were inserted between the PSi and TiO2 NPs to achieve GBQDSCs.